Analysis of Approaches to Controllership in Master’s Thesis from Post-graduate Programs in Accounting Sciences - Beuren, Ilse Maria; Bogoni, Nadia Mar; Fernandes, Luciano (Review of Business Management, 2008)
The objective of the study is to analyze approaches in master’s thesis in Brazilian Post-Graduate Programs in Accounting Sciences in relation to Controllership, in terms of their conceptual, procedural and organizational aspects, as proposed by Borinelli (2006). The research is descriptive and it uses a quantitative approach. The sample consists of 26 master’s thesis which have the word “Controllership” in their titles. Resulting from analysis, in Perspective I (conceptual aspects), in which the elements of definition, object of study and relationship with other sciences were referenced, consensus among authors of the master’s thesis was not verified. In Perspective II (procedural aspects), which deals with activities and functions of Controllership by means of how they materialize as areas of knowledge within organizations, it was observed that the approach in the master’s thesis is quite differentiated in terms of the scope of activities. In relation to Perspective III (organizational aspects), there is also no consensus about what constitutes typical Controllership activities, but master’s thesis do include in the definition of Controllership the idea that it is a service or function of information. It was concluded that the approach to controllership, in terms of its conceptual, procedural and organizational aspects is similar to the elements proposed by Borinelli (2006). Key-words: Approaches. Controllership. Master’s thesis. PPGCC.